Natural patterns of social support for physical activity participation in newly matched breast cancer survivor dyads - Serena S. Peck; Madison F. Vani; Jenna Smith-Turchyn; Catherine M. Sabiston (BMC, 2023)
Abstract Background Physical activity (PA) can be a beneficial strategy to mitigate physical, emotional, and social-related challenges in women living beyond breast cancer treatment (WBC). However, PA levels among WBC remain low. Optimizing social support provided in a peer-matched setting may increase PA behavior. Unfortunately, factors that lead to an ideal peer-match among WBC are not well understood. The purpose of this study was to contextualize the natural social support environment and PA behavior in newly formed peer WBC dyads participating in an ecological momentary assessment study. Methods WBC were matched with a partner and provided with a Fitbit activity tracker. Social support was measured using 21-daily surveys, and a 3-week follow-up survey. Descriptive statistics were calculated. Open-ended survey questions were analyzed using content analysis. Data were analyzed based on (i) social support types (informational, tangible, esteem, and emotional support); and (ii) WBC' reports of being in a good, neutral, or poor match at the end of the study. Results Women (n = 46; Mage = 42.4 ± 7.6 years; 89.2% stage I-III breast cancer) connected with their partner (58.1%) and participated in moderate-vigorous PA (MVPA)(77.1%) on most days over the 21-day study period. Women were identified as being in good (63%), neutral (20%), or poor (17%) dyad matches. The most frequently documented social support received by WBC was esteem support. Participants in a good match were more likely to report receiving all types of social support compared to neutral or poor matches. Conclusion & clinical implications Findings describe the social support characteristics important to WBC for facilitating their PA participation in a partner-based setting. This study provides valuable insight that can inform the development of partner-based PA interventions for WBC.